Scavengers and Their Awareness about National Scheme for Liberation and Rehabilitation (NSLRS) – A Case of Haryana: Awareness and Implementation of NSLRS Scheme among Scavengers in Urban Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present study is carried in the state of urban Haryana to know the awareness regarding rehabilitation scheme for scavengers launched by the central govt. with state govt. On the basis of location five district namely Ambala, Kurukshetra, Karnal, Panipat, Sonipat were selected with a view that due to effect of highway facilities there may be advancement in the standard of living and different areas of life. Purposive sampling was used in the present study and 415 respondents were selected from the universe i. e. 20% of the total respondents out of 2077 of the selected districts. The lists of the respondents were prepared with the help of the list published by SCDFC Haryana. The study revealed that the only 41.2 % respondents have known about NSLRs scheme. Only 35.7 % said that it is implemented in Haryana. The study exposed that the only15.4% respondents have knowledge about the following components of the scheme- subsidy, margin money and bank loan amount.